EVALUASI PENGELOLAAN SAMPAH PADA BANK SAMPAH DI DESA/KELURAHAN LARANGAN SIDOARJO - Dyah Ratri Nurmaningsih; Rita Ernawati (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2018)
Garbage is still seen by some people as waste that is not useful, not as a resource that can be utilized. The approach to reduce at source and recycle resources through the implementation of 3R is a more comprehensive waste management policy. Sidoarjo Regency as one of the buffer zones of Surabaya City on a daily basis produces a large volume of waste. Based on data from the Department of Sanitation and Landscaping of Sidoarjo Regency, waste management in the region has not been implemented comprehensively. Although around 100 units of Garbage Banks have been formed on a community scale, the operational activities of each unit have not been optimal. This study used descriptive qualitative method. Data was obtained by direct interviews with the Village / Village residents of the Prohibition and questionnaire, which were then analyzed. The amount of waste volume managed every month on average (Kg) shows a good amount. Waste waste is also used to increase the income of the waste bank customers in particular. Problems that occur both internal problems of institutions, technical problems, and problems outside the institution, internal problems of the institution that occur quite a lot is due to lack of awareness of the community to participate in waste management, while technical issues and problems outside the institution are not so significant. The existence of government support is needed in the sustainability of the waste bank in the Larangan District of Sidoarjo Regency, while the government support that has been implemented includes the provision of composter, supporting equipment, savings books and socialization to the community. Keywords: Garbage, waste management, waste bank.